Reading motivation of students in a secondary school in rural area of Johor - Ismail, Nurliyana (2012)
The problems of reading among Malaysians are worsening. Based on National Literacy Survey, it is proved that Malaysians hardly ever read. The Malaysia exam-oriented education system as well as the issue of reverting back to Malay language as the medium of instruction in schools were also the main concerns of this study. This study is conducted to find out the problems that learners face in reading in English and the factors that affect learners‘ motivation in reading. The study is also carried out to examine the way in which the factors affect learners‘ motivation in reading. Twelve learners of a rural secondary school in the district of Kulai were chosen for the interview sessions while 100 learners were randomly chosen for the quantitative data collection. The instruments used for this study were interviews and questionnaire. Results from the interviews conducted with twelve learners from different levels of English proficiency revealed that the lack of English reading resources especially in schools and their financial problems has hindered their access to their favourite reading materials. Learners also faced problems in comprehending certain texts, especially the difficult and complicated ones and they did not have adequate background knowledge related to the texts. The other problems revolved around vocabulary use, had difficulty with unfamiliar and unknown words and the lack of interest towards English reading materials. It was also discovered that there were 5 main factors that affect learners‘ motivation in reading namely intrinsic motivation, extrinsic motivation, competency and reading efficacy, social aspects for reading and encouragement from English teachers. Furthermore, extrinsic motivation factor was found as the most important factor to motivate learners (mean=3.86). It is hoped that the findings of the study would provide useful insights to the language teachers and educators, parents and school administrators in planning and executing their roles more efficiently in the future. This is to ensure that more learners especially from the rural schools would become more motivated to take up reading English books as a pastime as this would definitely help them become more proficient in English.